IMPLEMENTASI JARINGAN LORA DALAM MONITORING OIL TRAP BERBASIS IOT MENGGUNAKAN METODE RESEARCH AND DEVELOPMENT - Mukhsinin, Nuriel; Sitohang, Sunarsan (Computer Science and Industrial Engineering, 2024)
The shipyard industry is inseparable from work activities using liftting and heavy equipment and is related to liquid oil waste and oil waste treatment system, Oil traps in this case are in line with the SDGS goals in sustainable development to protect the environment. In the object of research, the oil trap system that runs is still done manually both in terms of monitoring and controlling the oil, there is need a technology that able to detect oil in real time based on the Internet Of Things, in this modern era the Internet Of Things has become very common in monitoring and control, another problem is the shipyard industry in the object of research has a very large working area, therefore long range network technology will be the best solution to solving this problem, this study aims to create a system that is able to monitor and ensure the oil trap system runs optimally and realtime in controlling liquid waste in a large work area with the implementation of the Internet Of Things-based LoRa network. Research and Development method used in this research in designing, developing, and testing oil trap monitoring systems is very suitable, effective and efficient. The system consists of LDR and Ultrasonic sensors connected via LoRa network using SX1278 module to send real-time data to Telegram bot. The test results show that the developed monitoring system is able to detect and transmit oil trap condition data accurately, with a wide transmission range. from these results, it can be concluded that the implementation of the LoRa network in Internet Of Things-based oil trap monitoring is effective and reliable. This research is expected to contribute to the development of environmental monitoring technology.